2012
DOI: 10.1002/smll.201202232
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐High Optical Absorption Efficiency from the Ultraviolet to the Infrared Using Multi‐Walled Carbon Nanotube Ensembles

Abstract: The optical absorption efficiencies of vertically aligned multi-walled (MW)-carbon nanotube (CNT) ensembles are characterized in the 350-7000 nm wavelength range where CNT site densities > 1 × 10(11) /cm(2) are achieved directly on metallic substrates. The site density directly impacts the optical absorption characteristics, and while high-density arrays of CNTs on electrically insulating and non-metallic substrates have been commonly reported, achieving high site-densities on metals has been challenging and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…The lattice parameter analysis seen in Fig. 3(e) indicated that several areas of the hybrid layer had a lattice distance equal to 0.23 nm, which corresponds to the 011 plane of Ni(OH) 2 , whilst the area shown in Fig. 3(f) had a lattice distance of 0.21 nm, corresponding to the 002 plane of NiO.…”
Section: 52mentioning
confidence: 99%
See 4 more Smart Citations
“…The lattice parameter analysis seen in Fig. 3(e) indicated that several areas of the hybrid layer had a lattice distance equal to 0.23 nm, which corresponds to the 011 plane of Ni(OH) 2 , whilst the area shown in Fig. 3(f) had a lattice distance of 0.21 nm, corresponding to the 002 plane of NiO.…”
Section: 52mentioning
confidence: 99%
“…Fig. 3(a) shows that MgO and Mg 2 SiO 4 were the major components of both samples, whilst Ni(OH) 2 and NiO made up a minor fraction of NiMO. The peak for Ni(OH) 2 was detected in several position, but the most prominent was at 2q value of 33 which was coming from diffraction of (101) plane, while NiO was at 2q value of 43.5 from the diffraction of (200) plane.…”
Section: 36mentioning
confidence: 99%
See 3 more Smart Citations